Time-Domain Greedy Heuristic Approximation Algorithm for Multi-channel Assignment in Wireless Mesh Network - Wei-wei, Zhang; Jia-feng, He; Guo-wang, Gao; Li-li, Ren; ShenXuan-jing (CyberC 2017 : proceedings, 2017 International Conference on Cyber-Enabled Distributed Computing and Knowledge Discovery : Nanjing, China 12-14, October 2017, 2017)
A wireless Mesh network is a multi-radio network with the uncertainty of node heterogeneity. This paper proposed a multi-channel allocation algorithm based on Time-Domain Greedy heuristic approximation algorithm. The main idea of this algorithm is to make use of the characteristics of different channels to work at the same time, withoutinterference withanother channel. It considers the different interfaces in the geographically distributed channels. The channel assignmentallows time slot to be allocated in parallel. This not only can improve the overall throughput of the whole network, but also can reduce the other overhead that caused by the time of channel reallocation and channel changes. The simulation results show that the algorithm is improved on the basis of the original, and achieves the desired effect.